HUBUNGAN DUKUNGAN TEMAN SEBAYA DENGAN MOTIVASI BERPRESTASI PADA SANTRI PESANTREN ISLAM AL-IRSYAD, KECAMATAN TENGARAN, KABUPATEN SEMARANG - ADDINA NURUL ULFAH; Jati Ariati (Jurnal EMPATI, 2017)
The success of students in education, one of them can be shown with academic achievement. The success of students in their education is also influenced by achievement motivation. This study aims to determine the relationship of peer support with achievement motivation at Al Irsyad Islamic boarding school. The population of this research men junior high school and women junior high school is 655 santriwan and 121 santriwati. The sample of this research are 227 santriwan and 89 santriwati obtained by cluster random sampling technique. Data were collected using Achievement Motivation Scale (24 valid items; α = .88) and Peer Support Scale (28 valid items; α = .89), which have been tested on 93 students. Simple regression analysis showed a positive and significant correlation between peer support and achievement motivation shown through correlation coefficient rxy = .397 with p = (p <0.001). The more positive peer support, the achievement motivation will be high. Peer support provides an effective contribution of 15.7% on achievement motivation. Additional analysis in this study used independent sample t-test, which showed that there were significant differences in peer support variables between male and female with t = -3.144 with significance of 0.002 (p <0.05), and there was no difference which is significant on achievement motivation variable between men and women with t = 0,159 with significance 0,605 (p> 0,05).